Inhibition of the long non‐coding RNA ZFAS1 attenuates ferroptosis by sponging miR‐150‐5p and activates CCND2 against diabetic cardiomyopathy. Issue 21 (5th October 2021) - Ni, Tingjuan; Huang, Xingxiao; Pan, Sunlei; Lu, Zhongqiu
Abstract: Diabetic cardiomyopathy (DbCM) is responsible for increased morbidity and mortality in patients with diabetes and heart failure. However, the pathogenesis of DbCM has not yet been identified. Here, we investigated the important role of lncRNA‐ZFAS1 in the pathological process of DbCM, which is associated with ferroptosis. Microarray data analysis of DbCM in patients or mouse models from GEO revealed the significance of ZFAS1 and the significant downregulation of miR‐150‐5p and CCND2. Briefly, DbCM was established in high glucose (HG)–treated cardiomyocytes and db/db mice to form in vitro and in vivo models. Ad‐ZFAS1, Ad‐sh‐ZFAS1, mimic miR‐150‐5p, Ad‐CCND2 and Ad‐sh‐CCND2 were intracoronarily administered to the mouse model or transfected into HG‐treated cardiomyocytes to determine whether ZFAS1 regulates miR‐150‐5p and CCND2 in ferroptosis. The effect of ZFAS1 on the left ventricular myocardial tissues of db/db mice and HG‐treated cardiomyocytes, ferroptosis and apoptosis was determined by Masson staining, immunohistochemical staining, Western blotting, monobromobimane staining, immunofluorescence staining and JC‐1 staining. The relationships among ZFAS1, miR‐150‐5p and CCND2 were evaluated using dual‐luciferase reporter assays and RNA pull‐down assays. Inhibition of ZFAS1 led to reduced collagen deposition, decreased cardiomyocyte apoptosis and ferroptosis, and attenuated DbCM progression. ZFAS1 sponges miR‐150‐5p to downregulate CCND2 expression. Ad‐sh‐ZFAS1, miR‐150‐5p mimic, and Ad‐CCND2 transfection attenuated ferroptosis and DbCM development both in vitro and in vivo. However, transfection with Ad‐ZFAS1 could reverse the positive effects of miR‐150‐5p mimic and Ad‐CCND2 in vitro and in vivo. lncRNA‐ZFAS1 acted as a ceRNA to sponge miR‐150‐5p and downregulate CCND2 to promote cardiomyocyte ferroptosis and DbCM development. Thus, ZFAS1 inhibition could be a promising therapeutic target for the treatment and prevention of DbCM.